An Aplication of the Sinergity Model of Intrepreneurship Development Through Small and Medium Enterprise Cooperatives in Makassar - Agussalim; Andi Rustam; Andi Arifwangsa Adiningrat; Arniati (Jurnal Economic Resource, 2021)
Small and Medium Enterprises tend to be superior and developed. Through the synergy model, it enabled to create excellence and improve its business as well as entrepreneurial development. The research was an applied research which aimed to measure the practicality of the form of the synergy model developed and to measure the effectiveness of the synergy model in developing entrepreneurship through Small and Medium Enterprise Cooperatives (SMEC). The research used an applied qualitative method. Techniques of data collection were library research, interviews and observations. The research instrument for the initial study, validation and tryout was used by a questionnaire for the community. Meanwhile, the application of the model used the achievement test for entrepreneurship development through SMEC. The results of the study showed that the design of the synergy model with the highest level of practicality was resources and marketing. The synergy model was very practical to use for actors who were starting new businesses or already running businesses. Business was very important for increasing workforce and economic growth. The synergy model in business development was very good to apply in entrepreneurial life. In entrepreneurship, it was important to pay attention to creativity, supporting factors, both material and non-material, the price of products, so that entrepreneurship ran smoothly. This synergy model was a reference in entrepreneurship development, and the most important thing was the action on the modeling.